The Shifts in the Translation of the main Character's Dialogue into Indonesian - salsabila, allya (Universitas Samudra, 2023)
Translation shifts are commonly observed in the context of translating literary works, primarily focusing on novels. However, in this study, the researcher examine translation shifts in the context of movie dialogues. the objective of this research is to categorize the various types of translation shifts and analyze their application in the English dialogues of the main character, as translated into Indonesian subtitles in the movie Crazy Rich Asians. This study employed a descriptive qualitative research method to gather and analyze the data. The data were obtained from the English version of Crazy Rich Asians and its corresponding Indonesian subtitles. Data collection involved a combination of observation and documentation techniques. Subsequently, we analyzed the collected data using theory of translation proposed by Catford (1965). The findings indicate the presence of multiple types of translation shifts. These shifts involve alterations in grammar to lexis, changes in the position of heads and modifiers, transformations from phrases to words, and the conversion of plural form into singular forms. This study confirms that translation shifts are not confines to novels but also extend to the realm of movie dialogues.